2018
DOI: 10.3390/land7040148
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Land Conversion, Land Economic Value, and Sustainable Agriculture: A Case Study in East Java, Indonesia

Abstract: Agricultural land conversion (ALC) is an incentive-driven process. In this paper, we further investigate the inter-relationship between land economic value (LEV) and ALC. To achieve this goal, we calculated the LEV for agricultural and non-agricultural (housing) uses in two areas of East Java, Indonesia. The first area represents peri-urban agriculture, which is facing rapid urbanization and experiencing a high rate of ALC. The second area represents rural agriculture, with zero ALC. Furthermore, we identified… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 128 publications
(95 citation statements)
references
References 58 publications
2
62
0
4
Order By: Relevance
“…For example, a study on tomato growers in Ghana revealed that the perception of climate variability drives farmer to use more agrochemicals to retain crop production, and these chemicals cause the pollution of nearby water bodies and increase soil acidity above the optimum crop requirements [18]. Similar practices have been identified in rural areas of Indonesia, where watermelon farmers use excessive chemical pesticides to retain production, causing groundwater pollution that damages the quality of water for consumption [92]. 1 Ultimately, adaptation becomes maladaptation, which erodes sustainable development and shifts vulnerability to other actors.…”
Section: Economics Factorsmentioning
confidence: 92%
“…For example, a study on tomato growers in Ghana revealed that the perception of climate variability drives farmer to use more agrochemicals to retain crop production, and these chemicals cause the pollution of nearby water bodies and increase soil acidity above the optimum crop requirements [18]. Similar practices have been identified in rural areas of Indonesia, where watermelon farmers use excessive chemical pesticides to retain production, causing groundwater pollution that damages the quality of water for consumption [92]. 1 Ultimately, adaptation becomes maladaptation, which erodes sustainable development and shifts vulnerability to other actors.…”
Section: Economics Factorsmentioning
confidence: 92%
“…The protection forests, production forests, plantation forests and perenniel crop gardens have reduced, while the land development for industries locations and human settlements have increased significantly [11;[12]; [13]; [14]; [15]. The development of the region, landuse planning and residential planning is needed with an assessment of land carrying capacity [16]; [17]; [18], so that economics development are in accordance with the carrying capacity and capability of land [19]; [20]; [21]; [22].…”
Section: Introduction (mentioning
confidence: 99%
“…That conversion was to be threat that potentially occurred in Sumberpitu water spring. Economic interest was main cause of land conservation [27]. Land conversion did not only occur in upper stream area, but also occurred in downstream area (surrounding rural, agricultural land, and urban).…”
Section: Water-human-land System As a Conceptual Model Of Springs mentioning
confidence: 99%